Seasonal variation of metazoan parasites of Geophagus brasiliensis (Perciformes: Cichlidae) from the Guandu river, State of Rio de Janeiro, Brazil - doi: 10.4025/actascibiolsci.v32i2.4883 - Carvalho, Adriano Reder (2010)
The present work studied the seasonal variation of the metazoan parasites of Geophagus brasiliensis from the Guandu river, State of Rio de Janeiro, Brazil. Four collections of 50 specimens of G. brasiliensis were accomplished between April 2006 and March 2007, in the different seasons. A total of 14 species of metazoan parasites were obtained: six trematodes (Crassicutis sp. in adult stage and five metacercariae, Austrodiplostomum compactum, Diplostomulum sp., Neascus type 1, Neascus type 2 and Posthodiplostomum sp.), three nematodes (Contracaecum sp. larval, Cucullanus sp. and Procamallanus (Procamallanus) peraccuratus adult); monogenean (Sciadicleithrum guanduensis); acanthocephalan (Neoechinorhynchus paraguayensis), larval glochidia; and hirudinean species of Glossiphonidae and Piscicolidae. With the exception of Glossiphonidae hirudinean, all parasite species showed prevalence and abundance peaks mainly in the spring sample, which could indicate seasonality of these parasite species in G. brasiliensis from the Guandu River.